Computed tomography imaging features of malignant ‘triton’ tumor to facilitate its clinical diagnosis: report of two cases - Yuan Li; Qiling Peng; Ning Jiang; David P. Molloy; Chun Zeng; Qingchen Wu (BMC Medical Imaging, 2022)
Abstract Background Malignant ‘triton’ tumor is an extremely rare subtype of malignant periphery nerve sheath tumors. Clinical diagnosis of malignant triton tumor is difficult before surgery due to its low incidence and the lack of knowledge. Therefore, to describe and summarize the CT imaging characteristics of malignant triton tumor is of great assistance for early and preoperative diagnosis. Case presentation Two cases suspected of MTT by CT scan before operation were closely observed. The diagnosis of malignant triton tumor was eventually confirmed by immunochemical assay, which verified speculation of CT scans. Huge, irregular, well-circumscribed lobulated mass-like shadows can be observed from these patients by CT scans. Besides, heterogeneity of density within the body of tumor was well-established by CT scans, together with linear septum. Meanwhile, CT scans demonstrated that calcifications were remarkable at the margin of tumor body. Conclusions Some CT image features from two cases were presented as a reference for the preoperative consideration of MTT: (i) enormity of mass-like shadow; (ii) presence of well-circumscribed lobulated shape; (iii) septum within the well-defined mass accompanied with hemorrhage, necrosis and cystic changes as well as calcification, especially within neurofibromatosis type 1 patients.